Guidance and Counseling Design For Workers in Creative Industry Sector - Sumardi, Kamin (INVOTEC, 2017)
Creative industry is one of sectors that most resistant to the economic crisis. The creative industry is a group of industries that relies on individual creativity, skill and talent that has ability to improve living standards and provide employment through creating ideas and exploiting copyright. To optimize their performance they need guidance and counseling which are appropriate to their characteristics and needs. The aim of this study is develop a model of guidance and counseling which is specific and relevant to the needs of workers in the creative industries. The study used research and development method. Additionally, the study used interviews and observations as the research instrument. The location of study was the district of creative industries in Bandung. The research subjects were 3 creative industries. The results of the study show that counseling system toward the employees has not been implemented comprehensively and sustainably. The guidance and counseling were implemented only on certain aspects related to the quantity and quality of the products. The guidance was implemented only by such industries and has not involved other parties. The conclusion of the study concludes that the creative industries need a model of guidance and counseling which would help them to develop their activities and products must be in accordance with national standard in order to be more competitive.